PERANCANGAN SISTEM INFORMASI MATERIAL PRODUKSI KULINER MENGGUNAKAN METODE FIRST IN FIRST OUT (FIFO) PADA X CAFE - Edy Rakhmat; Raden Kania; Khasan Asrori; Lona Noviani; Silvia Ayu Ananda (Journal of Innovation And Future Technology, 2026)
Inventory is an important aspect of a company to support the smooth running of its business activities. X Cafe is a company engaged in the culinary field located in Kec. Pontang, Kab.  Serang Banten. X Cafe sells several types of processed food and drinks with various flavours and the process of making the food menu is made by the cafe employee itself. X Cafe purchased the supplier to meet the supply of raw materials in the kitchen. At present the management of the current transaction recording still uses a conventional system, namely by bookkeeping, which still has weaknesses and obstacles in its business activities, such as errors in recording, data processing that is not real-time results in inventory information not known in detail and difficulties in making reports In the transaction of raw materials in and out. Therefore, it takes a raw material inventory information system that aims to overcome the constraints and weaknesses of the current system in the X Cafe. This study uses the waterfall method as a method of developing a system and the method of a unified modelling language (UML) as a model method. First in First Out (FIFO) method is a method of solving problems applied to the process of laying and taking raw materials to facilitate the activity of the entry of raw materials. The results of this study are a raw material inventory information system that is useful for managing and controlling raw material inventory and can facilitate the work of all parts related to well, fast, and in accordance with the desired needs using the First In First Out (FIFO) method